Improvement of Route-Planning Systems Using Intelligent and Knowledge-Based Methods - Ernst, Sebastian; Ligęza, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Route planning is one of the major successful applications of automated planning (AI planning), a branch of Artificial Intelligence. However, classical planning methods are often too general when it comes to adaptation to real-life conditions and situations. This article provides an overview and suggestions for improvement of route-planning systems, particularly those used in urban conditions, with the help of knowledge engineering and other intelligent techniques. It also describes a new approach to route planning, based on the granular set theory, aimed at maintaining a set of paths instead of a single one. Such approach can provide significant improvements in agility, as well as introduce interaction with the user. Numerous enhancements of existing informed search algorithms are provided, along with commentary and references. Furthermore, the article suggests new methods and approaches for urban route planning, such as pre-computation of alternative routes, including guidelines for formal representation, solution robustness analysis and map abstraction with regard to decision-making points.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 65-74